Evaluating a cardiovascular disease risk management care continuum within a learning healthcare system: a prospective cohort study. Issue 5 (December 2020) - Groenhof, T Katrien J; Lely, A Titia; Haitjema, Saskia; Nathoe, Hendrik M; Kortekaas, Marlous F; Asselbergs, Folkert W; Bots, Michiel L; Hollander, Monika
No abstract available